Revealing Name Givers’ Decision on Giving English First Name to Children in Rural Area - Sari, Sintani Fina (Language Horizon: Journal of Language Studies, 2024)
Names are used to distinguish one from another. This study analyzes the reason for the name giver to bestow their children with English name. This research uses the causal of name approach of Sa’ida (2021) to analyze the reason behind the naming process. The purpose of this study is to examine the factors that influence parents in rural areas when choosing English first name for their children. This research is a qualitative research with data of children born in 2019 to 2004 in Sawoo village and interview with the parents. The results of the study reveal the relationship between the relation to thoughts, feelings, and other factors (believe) that create a certain value, showing the important role of the name giver in naming children. Furthermore, the reasons for choosing names are divided into the following: namesake, meaning, rhyme, aesthetic, religious, moment, tradition, chance and no reason.